Analysis of Coastal Community Preparedness for The Tsunami Disaster (Case Study in Bulakan Village, Cinangka District, Serang Regency, Banten) - Erni Hofifah (Universitas Lambung Mangkurat, 2023)
Cinangka Sub-district in Serang Regency is one of the sub-districts affected by the 2018 Sunda Strait tsunami in Serang Regency. One of the villages in the Cinangka District that was affected by the Sunda Strait tsunami was Bulakan Village. The tsunami disaster is a disaster that occurred suddenly and resulted in many casualties, so the community must know what steps must be taken. This study aims to determine the level of preparedness of coastal communities in Bulakan Village, Cinangka District for Tsunami Disaster. This research uses quantitative methods. Determination of the sample using the Proportional Random Sampling method with a total sample of 92 respondents. Collecting data using questionnaires and interviews with respondents. The questionnaire used to measure the level of community preparedness for the tsunami disaster uses the LIPI-UNESCO/ISDR, 2006 standard with the parameters Knowledge and Attitude (KA), Emergency Response Plan (EP), Disaster Warning System (WS), and Resource Mobilization (RMC). . Based on the research results from the assessment of the parameters of knowledge and attitudes, policies, response plans, disaster warnings and resource mobilization for each RW of Bulakan Village, it can be concluded that the level of preparedness in RW 001 with the ready category is 67. The level of preparedness in RW 002 with the almost ready category is 62. The level of preparedness in RW 003 with the almost ready category is 60. The level of preparedness in RW 004 with the almost ready category is 63. The level of preparedness in RW 005 with the ready category is 69. The level of preparedness in RW 006 with the ready category is 70. Based on the four In this category, the overall preparedness of the Buakan Village community for the tsunami disaster is included in the very prepared category of 67.